Pengaruh Kualitas Layanan dan Harga terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan sebagai Variabel Intervensi di Barbershop danszid Sidoarjo - Moslem, Muhammad Emray; Rahma Ulfah Maghfiroh (Prodi Manajemen Zakat dan Wakaf, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2025)
This study aims to explore the relationship between service quality, customer satisfaction, and customer loyalty in the service sector. This research is not only expected to contribute to the development of service management theory, but also provide practical benefits for service companies. By understanding the factors that influence customer satisfaction and loyalty, companies can formulate more effective strategies in improving their services. This will ultimately help service companies to retain their customers, reduce marketing costs, and increase profitability. Overall, a focus on service quality, customer satisfaction, and customer loyalty is not only important for a company's short-term success, but also an investment for long-term success. Companies that are able to prioritize customer experience and provide superior service will have a stronger position in facing competition in an increasingly competitive market. This research is a type of quantitative research with data collection methods through questionnaires or questionnaires. The population in this study were consumers of Babershop DANZID in Sidoarjo and its surroundings, with a total of 50 respondents. Overall, this study shows that price and service have a positive and significant effect on individual consumer loyalty. In the test results found evidence that satisfaction has a negative and insignificant effect in the service variable on consumer loyalty. However, no significant evidence was found to support the idea that customer satisfaction can influence the effect of price on customer loyalty.Based on the results of hypothesis testing conducted, it is concluded that price does not have a significant effect on customer satisfaction (H1 is rejected), but has a positive and significant effect on customer loyalty (H2 is accepted). Service is proven to have a positive and significant effect on satisfaction (H3 accepted) and consumer loyalty (H4 accepted). Customer satisfaction also has a negative but significant effect on customer loyalty (H5 accepted). Meanwhile, price has no significant effect on loyalty through satisfaction as an intervening variable (H6 rejected), and service has a negative but insignificant effect on loyalty through customer satisfaction (H7 accepted).